MHC Class II-Restricted Epitopes Containing an Oxidoreductase Activity Prompt CD4+ T Cells with Apoptosis-Inducing Properties - Malek Abrahimians, Elin; Carlier, Vincent A.; Vander Elst, Luc; Saint-Remy, Jean-Marie R. (Frontiers in Immunology, 2015)
Abrogating an unwanted immune response towards a specific antigen without compromising the entire immune system is a hoped-for goal in immunotherapy. Instead of manipulating dendritic cells and suppressive regulatory T cells, depleting effector T cells or blocking their co-stimulatory pathways, we describe a method to specifically inhibit the presentation of an antigen eliciting an unwanted immune reaction. Inclusion of an oxido-reductase motif within the flanking residues of MHC-class II epitopes polarizes CD4+ T cells to cytolytic cells capable of inducing apoptosis in antigen presenting cells (APC) displaying cognate peptides through MHC class II molecules. This novel function results from an increased synapse formation between both cells. Moreover, these cells eliminate by apoptosis bystander CD4+ T cells activated at the surface of the APC. We hypothesize that they would thereby block the recruitment of cells of alternative specificity for the same autoantigen or cells specific for another antigen associated with the pathology, providing a system by which response against multiple antigens linked with the same disease can be suppressed. These findings open the way towards a novel form of antigen-specific immunosuppression.